Unlocking User Satisfaction: The Dynamic Impact of Service Quality, Brand Image, and Promotion on Gojek and Maxim - Lionthiene, Via; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to determine the influence of services quality, brand image, and promotion on customer satisfaction. This research uses an explanatory research type with a quantitative method. The sampling technique used is non-probability sampling with a purposive method applied to 300 respondents, dividen into 150 respondents for Gojek and 150 respondents for Maxim. The characteristics include using Gojek or Maxim online transportation services more than once, being 18 years old or older, and residing in Malang City. This research uses a sample data of 300 from the population of Gojek and Maxim customers in Malang City. The analysis used is IBM SPSS 25.0. This research employs SPSS 25 software by conducting ANOVA and multiple linear regression analysis. The results show that services quality partially has a positive and significant effect on customer satisfaction Gojek, while at Maxim partially service quality has no effect on customer satisfaction. Brand image partially has a positive and significant effect on customer satisfaction Gojek and Maxim. Promotion partially has a positive and significant effect on customer satisfaction Gojek, while at Maxim partially promotion has no effect on customer satisfaction.